First-Ever Stroke and Transient Ischemic Attack Incidence and 30-Day Case-Fatality Rates in a Population-Based Study in Argentina. Issue 6 (June 2016) - Bahit, M. Cecilia; Coppola, Mariano L.; Riccio, Patricia M.; Cipriano, Lauren E.; Roth, Gregory A.; Lopes, Renato D.; Feigin, Valery L.; Borrego Guerrero, Brenda; De Martino, Maximiliano; Díaz, Alejandro; Ferrante, Daniel; Funaro, Fernando; et al.
Abstract : Background and Purpose—: Epidemiological data about stroke are scarce in low- and middle-income Latin-American countries. We investigated annual incidence of first-ever stroke and transient ischemic attack (TIA) and 30-day case-fatality rates in a population-based setting in Tandil, Argentina. Methods—: We prospectively identified all first-ever stroke and TIA cases from overlapping sources between January 5, 2013, and April 30, 2015, in Tandil, Argentina. We calculated crude and standardized incidence rates. We estimated 30-day case-fatality rates. Results—: We identified 334 first-ever strokes and 108 TIAs. Age-standardized incidence rate per 100 000 for Segi's World population was 76.5 (95% confidence interval [CI], 67.8–85.9) for first-ever stroke and 25.1 (95% CI, 20.2–30.7) for first-ever TIA, 56.1 (95% CI, 48.8–64.2) for ischemic stroke, 13.5 (95% CI, 9.9–17.9) for intracerebral hemorrhage, and 4.9 (95% CI, 2.7–8.1) for subarachnoid hemorrhage. Stroke incidence was slightly higher for men (87.8; 95% CI, 74.6–102.6) than for women (73.2; 95% CI, 61.7–86.1) when standardized for the Argentinean population. Thirty-day case-fatality rate was 14.7% (95% CI, 10.8–19.5) for ischemic stroke, 24.1% (95% CI, 14.2–36.6) for intracerebral hemorrhage, and 1.9% (95% CI, 0.4–5.8) for TIA. Conclusions—: This study provides the first prospective population-based stroke and TIA incidence and case-fatality estimate in Argentina. First-ever stroke incidence was lower than that reported in previous Latin-American studies, but first-ever TIA incidence was higher. Thirty-day case-fatality rates were similar to those of other population-based Latin-American studies. Abstract : Supplemental Digital Content is available in the text.